MAXMUD QAShQARIYDIŃ «DEVONU LUǴATIT TÚRK» MIYNETINDE «BAS» KONCEPTI (naqıl-maqallar mısalında) - Mámbetalieva, Q.A. (SCIENCE and SOCIETY, 2025)
In this article, somatic units and phraseologisms found in one of the most valuable works of the 11th century - Mahmud Kashgari's «Devonu luğat it-turk» and many proverbs and sayings cited in it were analyzed from a linguocultural point of view. The article is of great importance in the development of the modern Karakalpak literary language, in the formation of language norms.
Keywords: “head” concept; somatism; concept; proverb; phraseologism; linguoculture